2013
DOI: 10.4314/agrosh.v12i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Training Needs of Cashew Farmers in Owan East Local Government Area of Edo State, Nigeria

Abstract: The study assessed the training needs of cashew farmers in Owan East ' training needs (r=0.489, p=0.05). In order to improve performance and increase productivity, adequate training is required for cashew farmers with respect to the identified areas where they indicated needs for training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…This finding implies that majority of the farmers were within their active years. This is similar to the findings of Adesiji et al, (2012) that reported that the mean age among cashew farmers was 46.5 years. The table shows that the majority of the maize farmers (97.6%) were male.…”
Section: Resultssupporting
confidence: 92%
“…This finding implies that majority of the farmers were within their active years. This is similar to the findings of Adesiji et al, (2012) that reported that the mean age among cashew farmers was 46.5 years. The table shows that the majority of the maize farmers (97.6%) were male.…”
Section: Resultssupporting
confidence: 92%